2008
DOI: 10.1177/0898264308324636
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Commonalities Between Adaptive Resources and Self-Enhancement in Older Adults' Comparative Judgments of Physical Activity

Abstract: Objective-This study examines the extent to which optimism, control beliefs and motivation, and downward social comparison contribute independently to the maintenance of older adults' positive self-evaluations in a functional domain.Method-Adaptive resources/strategies and life satisfaction were measured in personal interviews with 164 community-dwelling older adults. Participants judged their physical activity compared with the average person of their age and wore an accelerometer for 24 hours. Commonality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…As in prior research assessing older adults’ perceived physical activity (e.g., Bailis, Chipperfield, Perry, Newall, & Haynes, 2008; Ruthig & Chipperfield, 2007), participants were asked, “Thinking about the past few months, how would you rate your physical activity,” with responses ranging from 1 ( extremely inactive) through 7 ( extremely active ), with a midpoint of 4 ( moderately active ). Prior research has shown this measure to be significantly associated with other indices of perceived activity level among older individuals, including positive correlations with comparative estimates of physical activity levels (e.g., Bailis, Chipperfield, Perry, Newall, & Haynes, 2008; Hanson & Ruthig, 2012) and negative correlations with health-related activity restriction (e.g., Ruthig, Chipperfield, Newall, Perry, & Hall, 2007). More broadly, it is also positively correlated with older adults’ self-rated health and negatively correlated with the number of existing chronic health conditions (Ruthig et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…As in prior research assessing older adults’ perceived physical activity (e.g., Bailis, Chipperfield, Perry, Newall, & Haynes, 2008; Ruthig & Chipperfield, 2007), participants were asked, “Thinking about the past few months, how would you rate your physical activity,” with responses ranging from 1 ( extremely inactive) through 7 ( extremely active ), with a midpoint of 4 ( moderately active ). Prior research has shown this measure to be significantly associated with other indices of perceived activity level among older individuals, including positive correlations with comparative estimates of physical activity levels (e.g., Bailis, Chipperfield, Perry, Newall, & Haynes, 2008; Hanson & Ruthig, 2012) and negative correlations with health-related activity restriction (e.g., Ruthig, Chipperfield, Newall, Perry, & Hall, 2007). More broadly, it is also positively correlated with older adults’ self-rated health and negatively correlated with the number of existing chronic health conditions (Ruthig et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…PISC also implies identifying upward more frequently, comparers learn from and gain more hope of becoming like superior others (Lockwood & Kunda, 1997; Lange & Crusius, 2015;Webster, Duvall, Gaines, & Smith, 2003), all which should be associated with fewer withdrawal behaviors like quitting. Indeed, SC interpretations that are associated with enhanced self-evaluation have been shown to be positively related to attitude about life (Bailis et al, 2008), attitude about a relationship (B. P. Buunk & vanYperen, 1989), and fewer withdrawal behaviors (e.g., Carmona et al, 2008). Conversely, NISC implies upward contrast which can generate shame and unfavorable self-perceptions (Pounders et al, 2017), and such effects are likely to induce withdrawal behaviors (Kristofferson et al, 2018;Wiersema et al, 2012).…”
Section: Mediating Role Of Social Comparison Interpretationmentioning
confidence: 99%
“…For instance, older adults exhibit what is known as the subjective age biasfeeling younger than one actually is (Teuscher, 2009). Other research has shown that older adults self-enhance on physical attributes, and doing so can have a marked well-being benefit (Bailis et al, 2008). However, other research notes that self-enhancement in older adulthood is constrained by reality, and thus, people tend to self-enhance on attributes that afford some interpretive flexibility, such as ambiguous traits (vs. specific traits; Dunning et al, 1989).…”
Section: Changing the Ecology Versus Changing Motivationmentioning
confidence: 99%